Impact of quality corporate governance on firm performance: A ten year perspective - Muhammad Azeem; Masood ul Hassan; Rehana Kouser (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Corporate governance remained most discussed issue in the 2000s during accounting standard adoption, and Asian financial crisis. This study intends to contribute toward the impact of corporate governance features on the firm performance in presence of certain firm specific attributes and uncontrollable (macro) events: firm size, capital structure, adoption of accounting standards, and Asian financial crisis. In this study, corporate governance scores are calculated by adopting an index from earlier studies. This index consists of two sections: structure (ownership concentration and managerial ownership) and independence (board independence and audit committee independence). High scores for the index denote quality corporate governance and vice versa. By using the fixed effects estimation method of panel data of 50 largest (by market capitalization) companies (listed at Karachi Stock Exchange), we found quality corporate governance significantly determining firm performance. Leverage (measured by debt ratio) moderates the relationship between quality corporate governance and firm performance by implying stronger relation for high levered firms and negative relationship of governance scores with performance for the case of low levered firms, firm size (measures by log natural of total assets) also changes the intensity of relation for variables of study (stronger relation for larger firms but no relation for small size firms). However, adoption of accounting standards doesn't have any significant for the association between the governance scores and firm performance. This study targets to gauge the impact of governance features on the performance through composite governance scores.
Keywords: 330; corporate governance; firm performance; Pakistan; Karachi Stock Exchange